Motion discrimination in dementia with Lewy bodies and Alzheimer disease. (20th October 2015) - Landy, Kelly M.; Salmon, David P.; Galasko, Douglas; Filoteo, J. Vincent; Festa, Elena K.; Heindel, William C.; Hansen, Lawrence A.; Hamilton, Joanne M.
Abstract : Objective: Visual processing abilities of patients with dementia with Lewy bodies (DLB) or Alzheimer disease (AD) dementia were assessed psychophysically using a simple horizontal motion discrimination task that engages the dorsal visual processing stream. Methods: Participants included patients with mild dementia with DLB, AD dementia or Parkinson disease (PD) with dementia (PDD), without dementia with PD, and normal controls. Participants indicated the left or right direction of coherently moving dots that were embedded within dynamic visual noise provided by randomly moving dots. The proportion of coherently moving dots was increased or decreased across trials to determine a threshold at which participants could correctly indicate their direction with greater than 80% accuracy. Results: Motion discrimination thresholds of patients with DLB and PDD were comparable and significantly higher (i.e., worse) than those of patients with AD dementia. The thresholds of patients with AD dementia and patients with PD were normal. These results were confirmed in subgroups of patients with DLB/PDD and AD dementia with autopsy-confirmed disease. A motion discrimination threshold greater than 0.23 distinguished between DLB/PDD and AD dementia with 67% sensitivity and 85% specificity. Conclusions: Differential deficits in detecting direction of simple horizontal motion suggest that dorsal processing stream dysfunction is greater in DLB and PDD than in AD dementia. Therefore, impaired performance on simple visual motion discrimination tasks that specifically engage occipitoparietal brain regions suggests the presence of Lewy body pathology.